Odd-chain fatty acids as a biomarker for dietary fiber intake: a novel pathway for endogenous production from propionate - Weitkunat, Karolin; Schumann, Sara; Nickel, Daniela; Hornemann, Silke; Petzke, Klaus J; Schulze, Matthias B; Pfeiffer, Andreas Fh; Klaus, Susanne (The American journal of clinical nutrition, 2017)
The risk of type 2 diabetes is inversely correlated with plasma concentrations of odd-chain fatty acids [OCFAs; pentadecanoic acid (15:0) and heptadecanoic acid (17:0)], which are considered as biomarkers for dairy fat intake in humans. However, rodent studies suggest that OCFAs are synthesized endogenously from gut-derived propionate. Propionate increases with dietary fiber consumption and has been shown to improve insulin sensitivity. We hypothesized that OCFAs are produced in humans from dietary fibers by a novel endogenous pathway. In a randomized, double-blind crossover study, 16 healthy individuals were supplemented with cellulose (30 g/d), inulin (30 g/d), or propionate (6 g/d) for 7 d. In addition, human hepatoma cells were incubated with different propionate concentrations. OCFAs were determined in plasma phospholipids and hepatoma cells by gas chromatography. Cellulose did not affect plasma OCFA levels, whereas inulin and propionate increased pentadecanoic acid by ∼17% ( < 0.05) and 13% ( = 0.05), respectively. The effect on heptadecanoic acid was even more pronounced, because it was elevated in almost all participants by inulin (11%; < 0.01) and propionate (13%; < 0.001). Furthermore, cell culture experiments showed a positive association between propionate and OCFA levels ( = 0.99, < 0.0001), whereas palmitate (16:0) was negatively correlated ( = 0.83, = 0.004). Our data show that gut-derived propionate is used for the hepatic synthesis of OCFAs in humans. The association of OCFAs with a decreased risk of type 2 diabetes may therefore also relate to dietary fiber intake and not only dairy fat. This trial was registered at www.germanctr.de as DRKS00010121.